Peningkatan Kreatifitas dan Hasil Belajar Kewirausahaan melalui Metode Pembelajaran Demonstrasi Kegiatan Usaha - Didik Nurhadi (Edunusa: Journal of Economics and Business Education, 2021)
This research is based on the importance of increasing creativity and improving student learning outcomes in Entrepreneurship subjects in SMK. The purpose of this research is to increase students' creativity and learning outcomes by using the demonstration learning method of Business Activities conducted by Entrepreneurship Teachers at SMK YPM 1 Taman, Sidoarjo. This research is a Classroom Action Research, using four steps, namely: 1) planning, 2) action, 3) observation, and 4) reflection. The four steps were then carried out with two research cycles. The results showed that the demonstration learning method succeeded in increasing students' creativity and learning outcomes in Entrepreneurship Subjects, where in the first cycle the number of students who had creativity based on observations was 70%, and student learning outcomes were 70%. Furthermore, in the second cycle students' creativity increased to 90%, and student learning outcomes increased to 92%. These results imply that learning with this demonstration method effectively improves creativity and student learning outcomes in schools.